Computational Thinking (CT)-based Student Worksheet to Improve the Mathematical Literacy of Mathematics Prospective Teacher - Swasti Maharani; Vera Dewi Susanti; Tri Andari; Ika Krisdiana; Indra Puji Astuti (STAI Hubbulwathan Duri, 2023)
Mathematical Literacy ability has important for prospective mathematics teachers. It is closely related to Computational Thinking (CT). The aim of this study is to produce CT-students worksheets to improve the mathematical literacy of prospective mathematics teachers. The development study using model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Thirty-seven would-be maths teachers participated in the study's sixth semester. Subject criteria are students who are not familiar with CT. The instruments in this study were CT-based student worksheets, validation sheets, student response questionnaires, pre-test and post-test questions. The results showed that CT-based student worksheets met the criteria of valid (validity percentage of 84.5%), practical (practicality percentage of 88.68%), and effective (N-gain value of 46.91%). Based on these results, it's appropriate to conclude that CT-based student papers can help students who want to become math teachers learn more about math. Recommendations for further research can be made on the development of a wider material and a wider subject as well.